Enhancing athletic gymnastics training through the use of artificial intelli-gence - Shcherbin D.V.; Tretyakov A.A.; Putilina V.Yu.; Shilova M.V. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to assess the efficacy of AI-powered programs in amateur athletic gymnastics training. Methods and structure of the study. The research was conducted at the FIFTY GIM fitness center in Moscow. The participants were a woman and a man in their middle age, who regularly engaged in physical exercises. To evaluate the performance of AI-based programs, we proposed the following metrics: body weight and muscle mass were measured using the Omron BF-508 body composition monitor; heart rate and blood pressure were assessed using the Omron automatic tonometer; emotional state was evaluated using the SAN method. Results and conclusions. During the research, as part of the training with a coach, the indicators of muscle mass increased gradually, unlike when training with AI. The indicator of total body weight also changed in a similar manner. The changes in men’s indicators were not as rapid. We can say that no significant changes were observed during the study. However, in his opinion, he preferred classes with AI. Despite the sophistication of the software, human expertise remains crucial when designing physical education classes in sports. Perhaps a combination of both approaches would be the ideal solution. An experienced professional coach could use AI to clarify certain aspects.